ANALISIS YURIDIS PENDAFTARAN JAMINAN FIDUSIA UNTUK MENEGUHKAN KEPASTIAN HUKUM - Nurhan Nurhan (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2018)
The current legal arrangement of fiduciary guarantee still applies the provisions of Lawa Number 42Year 1999 regarding Fiduciary Guarantee. Since regulation of the minister of Justice and Human Rights of the Republic of Indonesia Number 10 of 2013 on the Electronic Fiduciary Guarantee Registration Procedure is pulished, the registration of fiduciary guarantee shall be done electronically (oline). So this study analyzed the juridical registration of fiduciary guarantee to confirm the legal certainty, whose research study was conducted in the Regional Office of the Ministry of Justice and Human Rights of the Republic of Indonesia Riau Islands Province.The results show that there are still obstacles in the implementation of elctronic fiduciary registration. Such as the incomplete application of the fiduciary guarantee registration system, and the implementation of the fiduciary guarantee removal provinsions, as well as the validity of the Fiduciary Guarantee Certificate. Therefore, it is hoped that the goverment and related institutions can issue legislation that provides legal certainty in the registration system. So there is a match between the provinsions of the Act (das sollen) with its implementation in the field (das sein).Keyword : registration, fiduciary guarantee, legal certainty